Prediksi Kemungkinan Default Obligasi Perusahaan yang Terdaftar di BEI - Ayu, Rara Astari Wulan; Herawati, Juni (Universitas Brawijaya, Indonesia, 2008)
his paper is aims to find out whether financial ratios as profitability ratio, solvability ratio, ratio of debt management, liquidity ratio and cash flow having ability to predict default risk of bonds and to identify ratio with the best influence to predict it. The research relies on a sample of 19 firms listed in Indonesia Stock Exchange over the 2003 until 2006 period and the logistic regression model is employed to analyze the relationship between dependent and independent variables to directly predict default risk This model found to have higher classification power and higher predictive accuracy. The result indicated that financial ratios were useful to predict default risk and those ratios had ability to predict default risk. The result of SPSS showed basic earning power, return on equity working capital to total assets, ratio of total debt to total assets, debt to equity ratio and current ratio had significant influence on predict probability of default bond. Moreover, the logistic regression identified basic earning power was the ratio which had the best influence to predict default risk. This result would be an alternative to the stake holders evaluating the performance of the firms and making decision for their financing or investment.